2013
DOI: 10.4056/sigs.3847890
|View full text |Cite
|
Sign up to set email alerts
|

Permanent draft genome sequence of Comamonas testosteroni KF-1

Abstract: Comamonas testosteroni KF-1 is a model organism for the elucidation of the novel biochemical degradation pathways for xenobiotic 4-sulfophenylcarboxylates (SPC) formed during biodegradation of synthetic 4-sulfophenylalkane surfactants (linear alkylbenzenesulfonates, LAS) by bacterial communities. Here we describe the features of this organism, together with the complete genome sequence and annotation. The 6,026,527 bp long chromosome (one sequencing gap) exhibits an average G+C content of 61.79% and is predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(27 citation statements)
references
References 98 publications
(119 reference statements)
1
26
0
Order By: Relevance
“…They found that the glycolysis is incomplete due to lack of the hexokinase and glucokinase genes so that the strain cannot utilize most types of sugars. Studies on the genomes of C. testosteroni strains ATCC 11996 [ 22 ] and KF-1 [ 23 ] showed the same results. We built metabolic pathway maps of 14 strains of C. testosteroni (including above strains) and showed that all genes for hexose phosphorylation were missed in all genomes of this species (Figure 6 ).…”
Section: Discussionmentioning
confidence: 68%
See 3 more Smart Citations
“…They found that the glycolysis is incomplete due to lack of the hexokinase and glucokinase genes so that the strain cannot utilize most types of sugars. Studies on the genomes of C. testosteroni strains ATCC 11996 [ 22 ] and KF-1 [ 23 ] showed the same results. We built metabolic pathway maps of 14 strains of C. testosteroni (including above strains) and showed that all genes for hexose phosphorylation were missed in all genomes of this species (Figure 6 ).…”
Section: Discussionmentioning
confidence: 68%
“…The draft sequences were submitted to GenBank Whole Genome Shotgun (WGS) database [ 27 ] and the accession numbers are shown in Table 1 . Genome sequences of four other C. testoteroni strains, CNB-2 [ 5 ], ATCC 11996 [ 22 ], KF-1 [ 23 ] and S44 [ 6 ] (Table 1 ) were obtained from the NCBI database. Genome sequences of eight strains of the Comamonadaceae family were also obtained from the NCBI database (Additional file 2 : Table S2).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…A taxonomic study using a polyphasic approach placed B. chironomi strain AIMA4 T in the genus Brachymonas within the family Comamonadaceae (Figure 1 ). The family Comamonadaceae comprises a larger number of genera (as shown in Figure 1 ) and a larger variety of species and phenotypes [ 15 ],[ 16 ].…”
Section: Organism Informationmentioning
confidence: 99%